E-health systems diffusion and use the innovation, the user and the Use IT model - Spil, Ton A. M.; Schuring, Roel. (Hershey : Idea Group Pub., 2006)
"This book gives an overview of models on the use and diffusion of information systems in the healthcare sector with particular attention to the role of the user"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information storage and retrieval systems -- Medicine -- Evaluation; Medical informatics -- Evaluation; Health services administration -- Information technology -- Evaluation; Medical care -- Information services -- Evaluation; Medical records -- Data processing -- Evaluation; Management information systems -- Evaluation; Information technology -- Psychological aspects; Diffusion of innovations; Physicians -- Attitudes; Computer literacy